ADAPTING ENGLISH INSTRUCTION: AN ANALYSIS OF NON-EFL STUDENTS’ LEARNING NEEDS - Agustiana, Vina; Rahmatunisa, Wulan; Darsih, Endang (University of Kuningan, 2023)
This study aimed to conduct a need analysis to examine the non-EFL students’ needs of English subject in university. This needs analysis covers English in general and in particular needed by the students. A quantitative research method was followed in the present study. Data was collected by using questionnaires. The items in the questionnaires addressed various issues; in other words, the emphasis was determining students’ lacks, wants and necessity on English subject. All new non-EFL undergraduate students at Kuningan University in academic year 2021/2022 involved in this study. They are from five different faculties; Faculty of Economy, Faculty of Teacher Training and Education, Faculty of Computer, Faculty of Law and Faculty of Forestry. Based on the results of questionnaires filled out by 421 students, it is known that, first, in relation to students’ lack on English subject, this study focuses on the competence of language skills and students' difficulties in mastering the four English skills. Most students assessed their English language skills competence at moderate level. Listening and speaking skills are assessed as the first priority followed by writing and reading skills. However, the research findings also show that speaking skills seem to be the most difficult skills for them apart from weak grammar and low vocabulary mastery. Second, related to the students’ wants on English subject, the preferred language skills are reading followed by speaking, listening and writing. Third, related to necessity on English subject, learning activities that students need to function effectively is to combine English and Indonesian as a medium in delivering material. Most students also think that learning English is better in large groups under the supervision of lecturers. Furthermore, feedback, revision, and reflection are very important aspects for developing the ability to self-regulate learning. Therefore, students prefer to be corrected immediately by the lecturer when they make mistakes. To achieve learning effectiveness, students also expect the integration of a variety of activities and the development of learning materials.